KEHIDUPAN SOSIAL EKONOMI PETANI JAGUNG DI NAGARI GERAGAHAN KAMPUNG TABUAH KECAMATAN LUBUK BASUNG KABUPATEN AGAM TAHUN 2007-2022 - Ridho Putra Pratama; Ranti Nazmi; Kaksim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the socio-economic life of corn farmers in Nagari Geragahan Kampung Tabuah, Lubuk Basung Subdistrict, Agam Regency, during the period 2007–2022 and to analyze the factors influencing the dynamics of farmers’ welfare. The research employed the historical method through the stages of heuristics, source criticism, interpretation, and historiography by utilizing archival records, agricultural statistical data, government documents, and interviews with farmers and related stakeholders. The findings show that during 2007–2017 corn production increased significantly, from an average of 4–6 tons to 10–15 tons, supported by government assistance in the form of seeds and fertilizers as well as relatively high corn prices ranging from IDR 2,000–5,000 per kilogram. This condition contributed to higher household income, improved housing conditions, asset ownership, and better access to education for farmers’ children. However, in the period 2018–2022 production declined by approximately 20% due to land conversion, unstable prices (IDR 2,000–3,000 per kilogram), weather factors, and reduced government support, which affected the economic stability of farming households. Overall, the socio-economic life of corn farmers experienced dynamic changes and continues to face structural challenges in maintaining sustainable welfare.